Sources of cadmium exposure among healthy premenopausal women - Adams, Scott V.; Newcomb, Polly A.; Shafer, Martin M.; Atkinson, Charlotte; Bowles, Erin J. Aiello; Newton, Katherine M.; Lampe, Johanna W. (The Science of the total environment, 2011)
Cadmium, a persistent and widespread environmental pollutant, has been associated with kidney function impairment and several diseases. Cigarettes are the dominant source of cadmium exposure among smokers; the primary source of cadmium in non-smokers is food. We investigated sources of cadmium exposure in a sample of healthy women. In a cross-sectional study, 191 premenopausal women completed a health questionnaire and a food frequency questionnaire. The cadmium content of spot urine samples was measured with inductively-coupled plasma mass spectrometry and normalized to urine creatinine content. Multivariable linear regression was used to estimate the strength of association between smoking habits and, among non-smokers, usual foods consumed and urinary cadmium, adjusted for age, race, multivitamin and supplement use, education, estimated total energy intake, and parity. Geometric mean urine creatinine-normalized cadmium concentration (uCd) of women with any history of cigarette smoking was 0.43 μg/g (95% confidence interval (CI): 0.38–0.48 μg/g) and 0.30 μg/g (0.27–0.33 μg/g) among never-smokers, and increased with pack-years of smoking. Analysis of dietary data among women with no reported history of smoking suggested that regular consumption of eggs, hot cereals, organ meats, tofu, vegetable soups, leafy greens, green salad, and yams was associated with uCd. Consumption of tofu products showed the most robust association with uCd; each weekly serving of tofu was associated with a 22% (95% CI: 11–33%) increase in uCd. Thus, uCd was estimated to be 0.11 μg/g (95% CI: 0.06–0.15 μg/g) higher among women who consumed any tofu than among those who consumed none. Cigarette smoking is likely the most important source of cadmium exposure among smokers. Among non-smokers, consumption of specific foods, notably tofu, is associated with increased urine cadmium concentration. ►Urine cadmium, usual diet, and smoking assessed in 191 healthy premenopausal women. ►Participants not occupationally exposed or expected to be highly exposed to cadmium. ►Any history of cigarette smoking associated with ~ 50% higher urine cadmium. ►Tofu products stood out as the food most robustly related to urine cadmium.